BIM-Based Life Cycle Sustainability Assessment for Buildings - Garcia-Martinez, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In recent years, the progress of digitization in the architecture and construction sectors has produced enormous advances in the automation of analysis and evaluation processes. This is the case with environmental analysis systems, such as the life cycle analysis. Methodology practitioners have found a fundamental ally in the building information modeling platforms, which allow tasks that conventionally consume large amounts of energy and time to be carried out more automatically and efficiently. In this publication, the reader will find some of the latest advances in this area.